2013
DOI: 10.1044/1092-4388(2012/11-0112)
|View full text |Cite
|
Sign up to set email alerts
|

Past Tense Production by English Second Language Learners With and Without Language Impairment

Abstract: Purpose: This study investigated whether past tense use could differentiate children with language impairment (LI) from their typically developing (TD) peers when English is children's second language (L2) and whether L2 children's past tense profiles followed the predictions of Bybee's (2007) usage-based network model. Method: A group of L2 children with LI (L2-LI) and a matched group of L2-TD peers were administered the past tense probe from the Test of Early Grammatical Impairment (Rice & Wexler, 2001) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
109
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(125 citation statements)
references
References 48 publications
16
109
0
Order By: Relevance
“…An alternative perspective is provided by Bybee’s usage-based network model (Bybee, 1995, 2003, 2006) as interpreted by Blom & Paradis (2013). Blom and Paradis (2013) provide a succinct description of their interpretation of a usage-based model of past tense acquisition by children with language impairments.…”
Section: Relationship Between Finiteness Marking and The Verb Lexiconmentioning
confidence: 99%
“…An alternative perspective is provided by Bybee’s usage-based network model (Bybee, 1995, 2003, 2006) as interpreted by Blom & Paradis (2013). Blom and Paradis (2013) provide a succinct description of their interpretation of a usage-based model of past tense acquisition by children with language impairments.…”
Section: Relationship Between Finiteness Marking and The Verb Lexiconmentioning
confidence: 99%
“…Blom and Paradis (2013) investigated whether L2 children with and without L1 delay differed in their acquisition of the English regular and irregular past tense or not. In terms of irregular verbs, the findings reveal that L2 children with normal development performed better than the other group.…”
Section: English Past Formsmentioning
confidence: 99%
“…In addition, Solt et al (2004) suggested that the main obstacle to correctly producing the three allomorphs of the '-ed' morpheme is the inability of L2 learners to perceive these allomorphs consistently. In recent years, there has been an increasing interest in the study of the English regular past tense verbs in different aspects, from child language acquisition (Blom & Paradis, 2013) to adult language acquisition (Birdsong & Flege, 2001;Solt et al, 2004;Lardiere, 2002;Sriphrom & Ratitamkul, 2014;Prapobaratanakul & Pongpairoj, 2016). However, far too little attention has been paid to regular past tense verbs by Thai scholars.…”
Section: Introductionmentioning
confidence: 99%
“…A minimum number of exposures to the target form seemed to be required; greater rates of exposure led to more accurate production. Others examining second language learners have also observed that Past Frequency and Lemma Frequency separately contribute to accuracy levels (Blom & Paradis, 2013). Second language learners may have less exposure to English and smaller verb vocabularies.…”
Section: Resultsmentioning
confidence: 99%
“…Work with bilingual and ESL populations suggests that frequency influences morphological production across the lifespan (Blom & Paradis, 2013; Nicoladis, Palmer, & Marentette, 2007; Wulff, Ellis, Roemer, Bardovi-Harlig, & LeBlanc, 2009). …”
Section: Lexical Frequencymentioning
confidence: 99%